Discovering Tutankhamun : from Howard Carter to DNA / Zahi Hawass. - Hawass, Zahi A. (Cairo ; New York : The American University in Cairo Press, 2013)
Penned by a scholar who was personally involved in research into the enigmatic young pharaoh, this comprehensive and fully illustrated new study reviews the current state of our knowledge about the life, death, and burial of Tutankhamun in light of the latest investigations and newest technology. Zahi Hawass places the king in the broader context of Egyptian history, unravelling the intricate and much debated relationship between various members of the royal family, and the circumstances surrounding the turbulent Amarna period.
The golden age of Egypt: Dynasty 18 -- Religion and life after death -- Robbers in the Valley of the Kings -- The tomb and its treasures -- Tutankhamun's mummy -- The discovery of the family of Tutankhamun -- The Valley of the Kings and finds after the discovery of Tutankhamun -- The curse of Tutankhamun -- Tutmania -- Conclusion.
Includes bibliographical references (pages 254-258) and index.
Keywords: Tutankhamen, -- King of Egypt; Egypt -- Civilization -- To 332 B.C.; Egypt -- Antiquities